Answer:
cos x (2 sin x − 1)
Step-by-step explanation:
sin(2x) − cos x
Use double angle formula.
2 sin x cos x − cos x
Factor.
cos x (2 sin x − 1)
Answer:
sinx
Step-by-step explanation:
hello :
note :
for all x in ℝ : 1) sin(x+2π) = sinx 2) sin(π-x) = sinx
in this exercice :
3π - x = 2π+(π - x)
sin(3π - x) = sin(2π +(π - x)) =sin(π-x) = sinx
Answer:
59
Step-by-step explanation:
Simplify the following:
5 + 9 (2 + 4)
2 + 4 = 6:
5 + 9×6
9×6 = 54:
5 + 54
5 + 54 = 59:
Answer: 59
Answer:
Here is the full proof:
AC bisects ∠BCD Given
∠CAB ≅ ∠CAD Definition of angle bisector
DC ⊥ AD Given
∠ADC = 90° Definition of perpendicular lines
BC ⊥ AB Given
∠ABC = 90° Definition of perpendicular lines
∠ADC ≅ ∠ABC Right angles are congruent
AC = AC Reflexive property
ΔCAB ≅ ΔCAD SAA
BC = DC CPCTC
I got 6x+3
The three equations are:
(2x-6) + (3x+1) + (x+8) =perimeter
2x+3x+x/1x=6x
-6+1+8= 3